Psychometric properties of the Sport Courage Scale for Chinese athletes - Gao, Shenmao; Guo, Zeyou; Zhang, Renfang; Jin, Junze; Dou, Guangbo (Frontiers in Psychology, 2023)
Objective: To revise Sport Courage Scale (SCS) suitable for Chinese athletes. Methods: 683 athletes were selected for verification factor analysis, correlation analysis, reliability analysis, and independent sample t-test using the method of random sampling of the entire group. Results: Confirmatory factor analysis model showed that model 1 (25 items) failed to fit the data; while model 2 (20 items) was finally accepted with its five-factor model. The factor structure consists of 5 dimensions (χ2/df = 2.262;CFI = 0.969;TLI = 0.963; RMSEA = 0.043; SRMR = 0.044). Cronbach's α of the final version of SCS was 0.845, and the corrected correlation coefficient between the items and the total score of the scale was between 0.352 and 0.788. Conclusion: Revised SCS has good reliability and validity and can be used as a measurement tool for the sports courage of athletes in China.